Social Support and School Success - Buzaitytė-Kašalynienė, Jolita (Acta Paedagogica Vilnensia, 2005)
Scientific problem refers to the lack of investigations that provide answers to the question if school success depends on perceived social support, is it possible to increase grades, attendance and positive behaviours by increasing social support from parents, teachers and class teachers. The purpose of the research is to reveal peculiarities of perceived social support and school performance schools. The aim of this article is to reveal the influence of social support on grades, attendance and behaviour in the school. The research was carried out applying the following research methods: analysis of scientific literature, survey research, statistical data analysis. It was developed students survey questionnaire with 236 multiple-choice items. These items address students' self-assessments of their beliefs about their social environment – neighbourhoods, schools, friends, and families - and about their own psychological health and school performance. The research is based on the answers of 1071 students (577 boys and 494 girls) of eighth grade. The paper reports only part of the research results. Data analysis reveals that higher parent's, teacher's and class teacher’s social support are associated with better school performance: attendance, grades, and behaviour, so social support defined as a protective factor. Protective factors are generally strengths that are present in individuals or in the environments and they help reduce the impact of the risks. Feeling that you supported and resources from caring relations contribute to children's school success. Caring families protect children from school failure by strengthening confidence, ability to overcome difficulties and school problems. Caring teachers and class teachers protect children by ensuring healthy teacher-student relationship, student's self-esteem, motivation and interest in the teaching subjects that increases grades, attendance and behaviour and decreases a possibility of school failure.
Keywords: social support and school success; attendance; behavior; motivation